2014
DOI: 10.1002/cne.23629
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bladder and colon afferents in the nodose ganglia of male rats

Abstract: The sensory neurons innervating the urinary bladder and distal colon project to similar regions of the central nervous system and often are affected simultaneously by various diseases and disorders, including spinal cord injury. Anatomical and physiological commonalities between the two organs involve the participation of shared spinal-derived pathways, enabling mechanisms of communication between the bladder and colon. Prior electrophysiological data from our lab suggests that the bladder also may receive sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 130 publications
1
34
1
Order By: Relevance
“…In the normal un‐operated control dogs, we found no evidence for sensory or motor vagal innervation of the urinary bladder, urethral sphincter, anal sphincter nor clitoris. This is in contrast to findings in the normal control Wistar rat in which substantial electrophysiological and anatomical evidence exists for vagal innervation of the urinary bladder, distal colon, uterus, cervix, and vagina . Studies recording brain activity during bladder filling using fMRI find no evidence of vagal innervation of the urinary bladder in healthy female volunteers, or in female patients with urinary frequency .…”
Section: Discussioncontrasting
confidence: 93%
“…In the normal un‐operated control dogs, we found no evidence for sensory or motor vagal innervation of the urinary bladder, urethral sphincter, anal sphincter nor clitoris. This is in contrast to findings in the normal control Wistar rat in which substantial electrophysiological and anatomical evidence exists for vagal innervation of the urinary bladder, distal colon, uterus, cervix, and vagina . Studies recording brain activity during bladder filling using fMRI find no evidence of vagal innervation of the urinary bladder in healthy female volunteers, or in female patients with urinary frequency .…”
Section: Discussioncontrasting
confidence: 93%
“…In painful diabetic neuropathy animal model, enhanced somatosensory pain perception was associated with increased expression and function of both tetrodotoxin (TTX)-sensitive Na v 1.7 and TTX-resistant Na v 1.8 sodium channels (Hong et al , 2004). Here we examined the expression of Na v 1.7 and Na v 1.8 in L4-L5 DRGs of control and WA stressed rats by immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…Corticosterone also increased the expression levels of Na v 1.7 and Na v 1.8 sodium channels in L4-L5 but not L6-S2 DRGs in vitro , supporting a “hard-wired” mechanism in DRG neurons. This differential response may reflect the distinct development fates of these DRGs and/or the bidirectional influence of the target organs, including the colon and bladder compared to the somatosensory distribution (Herrity et al , 2014;La et al , 2011;Christianson et al , 2007). Future studies will need to examine whether stress-response transcription factor binding sites (for example, GR binding regions) demonstrate altered epigenetic regulation, such as enhanced methylation in L4-L5 DRGs which could explain the absence of response in CB1 gene expression to chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, axotomy of the glossopharyngeal and carotid sinus nerves in the rat (innervating head and neck structures) results in down-regulation in the number of neurons expressing CGRP protein (Helke and Rabchevsky 1991) and transcript (Huang et al 1994). Axotomy of the vagus nerve, innervating the entire length of the gut (Grundy 2006), including the urinary bladder and the distal colon and rectum (Herrity et al 2014), has been shown to reduce the number of nodose ganglion neurons expressing CGRP transcript (Huang et al 1994), but not protein (Helke and Rabchevsky 1991). Here, we demonstrate that axotomy of the L6-S1 trunk results in downregulation of the number of CGRP-IR DRG neurons in the mouse.…”
Section: Discussionmentioning
confidence: 99%